Testing the Germ Number on Tableware at Roadside Stall Mas Joko in Palu City in 2021 - Atikah Pratiwi; Finta Amalinda; Eka Prasetia Hati Baculu; Irfan (Universitas Muhammadiyah Palu, 2022)
Cutlery is one factor that plays a role in transmitting disease because eating utensils that are not clean and contain microorganisms can share conditions through food (foodborne illness). The purpose of this study was to determine the test results for the number of germs on tableware at Roadside stall Mas Joko in Palu City in 2021. The type of research was descriptive with an observational approach. With a total of 8 samples from Roadside stall Mas Joko in Palu City. The results of the examination of samples taken at Roadside stall Mas Joko, Palu City, it was found that install one the inspection of the plate sample was 372 CFU/cm2, the glass sample was 420 CFU/cm2, Roadside stall 2 plate sampled 290 CFU/cm2, the glass sample was 353 CFU/cm2, stalls 3 sample plates 148 CFU/cm2, glass samples 363 CFU/cm2, and stalls 4 sample plates 465 CFU/cm2, glass samples 371 CFU/cm2. Based on the results obtained, it can be said that the tableware in the four Roadside stall Mas Joko has not met the requirements; this is based on the Minister of Health No. 1096 of 2011 concerning hygiene sanitation of catering services, which requires all tableware to be 0 CFU/cm2. Suggestions For the Puskesmas, especially sanitation installations, it is better to routinely provide counselling to food stall owners to always pay attention to the cleanliness of their eating utensils by Permenkes No. 1096 of 2011 concerning Hygiene Sanitation for Catering services which require tableware to be 0 CFU/cm2.